Commentary on the Apocalypse - Oecumenius, Bishop of Tricca (Fathers of the church, 2006)
"This is the first complete translation in English of Oecumenius's commentary, which is the first known Greek commentary on the book of Revelation. Written in the sixth century but discovered only at the beginning of the twentieth, it presents a fascinating view of a writer who strove to be faithful to the teaching of the church while at the same time allowing his imagination to make sense of the stories and visions of Revelation. In interpreting the events surrounding the destruction of the wicked he shows sensible pastoral restraint and refuses to be swayed by the dogmatic certainty shown even by some modern interpreters." "The introduction to the translation by John N. Suggit provides a brief account of the identity of the author and the theological issues with which he was involved, especially the controversy over the beliefs of Origen and his followers." "The book should be of interest not only to serious scholars, but also to those who are ready to listen to this New Testament book not as a record of past history but as the description of the drama of life today."--Jacket.